THE USE OF THE DECISION-MATRIX METHOD IN MARITIME TRANSPORT (Perner's Contacts, 2017)
The subject of the paper is the selection of the most suitable variant of transport between Southeast Asia and Slovakia using the decision-matrix method. Four major European seaports were selected for the comparison. The Asian port of Singapure is set as the starting point.
Keywords: maritime transport; decision-matrix method; transport route